2023
DOI: 10.1177/02841851231198349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influencing factors for artifact development in breast MRI-derived maximum intensity projections

Lorenz A Kapsner,
Eva L Balbach,
Frederik B Laun
et al.

Abstract: Background Magnetic resonance imaging (MRI) provides high diagnostic sensitivity for breast cancer. However, MRI artifacts may impede the diagnostic assessment. This is particularly important when evaluating maximum intensity projections (MIPs), such as in abbreviated MRI (AB-MRI) protocols, because high image quality is desired as a result of fewer sequences being available to compensate for problems. Purpose To describe the prevalence of artifacts on dynamic contrast enhanced (DCE) MRI-derived MIPs and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Within this period, female patients with a clinically indicated breast MRI performed with a full diagnostic protocol including CE sequences at the Institute of Radiology of the University Hospital Erlangen (UHE) were included in this study. The study sample is partially overlapping with previously reported cohorts in which (a) the automated detection of MRI artifacts on breast CE-MIPs by applying DL methods 19 and (b) a DL-based image quality assessment in high b-value diffusion-weighted breast MRI 20 were evaluated, as well as (c) an investigation of the prevalence of MRI-artifacts in breast CE-MIPs 21 . Details on the MRI protocols are given in supplement S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Within this period, female patients with a clinically indicated breast MRI performed with a full diagnostic protocol including CE sequences at the Institute of Radiology of the University Hospital Erlangen (UHE) were included in this study. The study sample is partially overlapping with previously reported cohorts in which (a) the automated detection of MRI artifacts on breast CE-MIPs by applying DL methods 19 and (b) a DL-based image quality assessment in high b-value diffusion-weighted breast MRI 20 were evaluated, as well as (c) an investigation of the prevalence of MRI-artifacts in breast CE-MIPs 21 . Details on the MRI protocols are given in supplement S1 .…”
Section: Methodsmentioning
confidence: 99%